0
$\begingroup$

Let $X~\sim B(n,p)$ be a binomial random variable. Calculate $E[X(X-1)]$.

Do I need to use the Binomial theorem? If yes, how?

$\endgroup$
2
$\begingroup$

$$E[X(X-1)]$$ $$=\sum_{x=0}^nx(x-1){n\choose x}p^xq^{n-x}$$ $$=\sum_{x=2}^nx(x-1)\frac{n!}{x!(n-x)!}p^xq^{n-x}$$ $$=n(n-1)p^2\sum_{x=2}^n\frac{(n-2)!}{(x-2)!(n-x)!}p^{x-2}q^{n-x}$$ $$=n(n-1)p^2(p+q)^{n-2}$$ $$=n(n-1)p^2$$ Note that $x(x-1)=0$ for both $x=0$ and $x=1$, so the range of summation an be taken as $x=2,3,\dots,n$; after factoring $n(n-1)p^2$ through the summation, the remaining sum is just $(p+q)^{n-2}$ from the binomial theorem.

$\endgroup$
  • $\begingroup$ Thank you. Now what is $X$'s variance? $\endgroup$ – E Be May 13 '15 at 16:43
  • 1
    $\begingroup$ The variance is $E[X(X-1)]+\mu_X-\mu_X^2=E[X(X-1)]-\mu_X(\mu_X-1)$. Thus it is $n(n-1)p^2-np(np-1)=np(1-p)=npq$. $\endgroup$ – Gregory Grant May 13 '15 at 16:45
  • 1
    $\begingroup$ I'm using $\sigma_X^2=E[X^2]-E[X]^2$. Where $\mu_X=E[X]$. $\endgroup$ – Gregory Grant May 13 '15 at 16:47
8
$\begingroup$

Hint: It is $E(X(X-1))=E(X^2)-E(X)$.

And $Var(X)=E(X^2)- [E(X)]^2 \Rightarrow E(X^2)=Var(X)+[E(X)]^2$

$\endgroup$
  • $\begingroup$ I don't understand why $E(X(X-1))=E(X^2)-E(X)$. Could you help me see it? $\endgroup$ – E Be May 13 '15 at 16:42
  • 1
    $\begingroup$ @UdiBehar It's true in general that $E[X+Y]=E[X]+E[Y]$. That's true even if $X$ and $Y$ are dependent. $\endgroup$ – Gregory Grant May 13 '15 at 16:43
  • 1
    $\begingroup$ @UdiBehar $E(X(X-1))=E(X^2-X)=E(X^2)-E(X)$ $\endgroup$ – callculus May 13 '15 at 16:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.